The Urgency of Publication in Intellectual Property Issuance in Indonesia - Herlambang Adhi Nugroho; Ampuan Situmeang; Elsa Syarief (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The trademark "I AM GEPREK BENSU SEDEP BENEERRR," which has the rights to industrial designs and is registered with the Director General of Intellectual Property (KI) and has been used since April 2017, has similarities with the Geprek Bensu brand. In this study, there are 2 (two) points that are the subject of the study of the problem, namely how to publish industrial designs and trademarks in Indonesia and what is the right solution so that industrial designs and trademarks in Indonesia are not published in duplicates. In answering these problems, the author uses a normative juridical approach. The results of this study are that the issuance of industrial designs and trademarks is carried out based on early registration. In order to avoid the existence of similarities in society, it is necessary to publish massively in various media.